The transcendence of desire: a theology of political agency - James, Thomas A. (New Approaches to Religion and Power, 2023)
1. Introduction: The Politics of Death -- 2. Renewing Political Agency: Arendt on Natality and Judgment -- 3. Theology's Re-politicizing: Crisis and Critique -- 3. Transcendence in a Secular Age: Cruciform Desire -- 4. The Problem and Promise of Politics -- 5. Prophetic Agency -- 6. Practical Agency -- 7. The Church as a Community of Desire.